An Innovative Technique based on Topical Modeling for Personalized Movie Searched Engine - Birla, Lokendra; Dhangar, Rohit; Kumar, Anand; Singh, Yogesh (International Journal of Engineering and Technology, 2018)
A large an amount of information is becoming available and this information is valuable source of intelligence but it is very difficult to extract or mine useful information for making decision. To overcome this type of problem, there are information filtering systems, such as Â the personalized movie searched engine (PMSE). This PMSE identifying interest of person on his/her preferences. This PMSE utilized userâ€™s reviews to create a personalized profile of user. First of preprocess the reviews then use Latent Dirichlet Allocation (LDA) for generating topic from user reviews. Finally, Dual Personalized Ranking function (D-PR) [1] will rank movies when the user enters a query. Experiment result shows that our system is able to give personalized movie search results to the user.Â Â Â